2014
DOI: 10.1007/s00134-014-3348-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinct determinants of long-term and short-term survival in critical illness

Abstract: We observed two phases of survival related to critical illness. Short-term mortality was mainly determined by the acute illness, but its effect decayed relatively rapidly. Mortality beyond 3 months, among those who survived to that point, was mainly determined by age and comorbidity. Recognition of these findings is relevant to discussions with patients and surrogates about achievable goals of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 35 publications
6
67
0
6
Order By: Relevance
“…continued from Table 3 In some situations, surgical intervention is necessary in the case of fractures among the elderly, and the intensive therapy unit is the site of immediate post-surgical recovery for the most severe cases, which in the present study were considered as hospitalizations for surgical reasons. However, hospitalizations for clinical reasons appeared as a risk in the survival table and in the multiple Cox model, a finding also obtained by other studies 12,14,18 . It is therefore assumed that the elective and controlled nature of non-emergency surgical procedures guarantee lower mortality than clinical events that usually affect the elderly in an acute and unexpected way.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…continued from Table 3 In some situations, surgical intervention is necessary in the case of fractures among the elderly, and the intensive therapy unit is the site of immediate post-surgical recovery for the most severe cases, which in the present study were considered as hospitalizations for surgical reasons. However, hospitalizations for clinical reasons appeared as a risk in the survival table and in the multiple Cox model, a finding also obtained by other studies 12,14,18 . It is therefore assumed that the elective and controlled nature of non-emergency surgical procedures guarantee lower mortality than clinical events that usually affect the elderly in an acute and unexpected way.…”
Section: Resultssupporting
confidence: 83%
“…This period of time is justified by the fact that international studies of survival usually consider two groups of predictors of mortality: impacting factors that have an effect in up to 30 days, known as short-terms; and long-terms, which are variables that impact survival after 30 days from the date of admission. It was also observed in other studies that the average length of hospitalization of the elderly in ICUs, including standard deviations, is around 20 days [11][12][13] . Remaining faithful to these assumptions is important for discussion and comparison between different studies.…”
Section: Methodssupporting
confidence: 64%
See 1 more Smart Citation
“…6 Some argue that this late mortality is simply a reflection of the underlying comorbidity burden of patients who develop sepsis, whereas others argue it is the result of sepsis itself. [7][8][9][10] Previous studies have provided evidence on both sides of the debate. Several studies explicitly assert that late mortality after critical illness is largely because of pre-existing comorbid disease.…”
Section: Introductionmentioning
confidence: 99%
“…The observational cohort study published by Garland et al (1) looked to identify which determinants were responsible for short-term and long-term survival in adult patients admitted to intensive care units. They found that with respect to long term mortality i.e., post 90-day mortality the most important determinants were age and co-morbidity, characteristics of the acute illness came a distant third (one major limitation of this study however is that it assessed unselected patients admitted to intensive care units, without specific focus on sepsis).…”
mentioning
confidence: 99%